The role of Radio-Télévision Libre des Mille Collines in the Rwandan genocide : An analysis from the theoretical perspectives of intergroup threat and aggression - Gustave Adolphe Messanga; Marios Yannick Duclair Tajeugueu (International Journal of Social Service and Research, 2023)
This research focuses on the role of Radio-Télévision Libre des Mille Collines (RTLM) in the Rwandan genocide. It analyzes the radio broadcasts through the prism of theories of intergroup threat and aggression. In this perspective, this medium is conceived as a manipulative and propagandist agent which participated in the perpetration of mass killings constituting the Rwandan genocide, through the dissemination of the ideology of hatred before and during the genocide and the logistical assistance provided to those involved in the killings. Indeed, RTLM broadcasts were structured in such a way as to present the Hutu as victims (intergroup threat), with the aim of justifying the use of violent actions against Tutsi (intergroup aggression). The corpus to be analyzed consists of extracts from RTLM broadcasts selected from transcripts stored at the Montreal Institute of Genocide and Human Rights Studies (MIGS) and at the International Monitor Institute (IMI). These extracts were analyzed with the method of discourse analysis. They reveal that RTLM’s discourse was based on the victimization and glorification of Hutus, as well as the devaluation and demonization of Tutsis. Concretely, the radio broadcasts were structured in such a way as to incite Hutu (past and present victims of injustice) to exterminate Tutsi (the enemies, the "cockroaches" (inyenzi)) and to eradicate them from Rwandan society. They were built around two main themes, including the threat, which includes elements like propaganda and hatred, homogenization, categorization and victimization ; and aggressiveness which includes the revolutionary vision of Rwanda, the deshumanization of Tutsi, their designation as enemies, the search for a just and homogeneous society.